A Quantitative Enzyme Immunoassay for Primary Fibrinogenolysis Products in Plasma - Koppert, P W; Kuipers, W; Nobel, B Hoegee-de; Brommer, E J P; Koopman, J; Nieuwenhuizen, W (Thrombosis and Haemostasis, 1987)
We have developed a two-step enzyme immunoassay (EIA) that allows the quantitation of degradation products derived from fibrinogen (FbgDP) and that does not detect degradation products derived from cross-finked (XDP) or noncrosslinked fibrin (fdp).The EIA is based on two monoclonal antibodies (FDP-14 and Y-18), developed in our institute. FDP-14 is used as catching antibody. It complexes exclusively with degradation products, irrespective whether these are derived from fibrinogen or from fibrin. It does not complex with intact fibrinogen or fibrin. Y-18 is reactive with fibrinogen and fibrinopeptide A-comprising fibrinogen fragments. It is used, conjugated with horse-radish peroxy-dase, as tagging antibody.The FbgDP-EIA is highly specific, accurate and sensitive. The coefficient of variation is between 3 and 8%; the lower detection limit is less than 0.025 μg/ml.The assay has been applied to plasma from patients with suspected disseminated intravascular coagulation (DIC), to plasma from patients undergoing streptokinase (SK) therapy for acute myocardial infarction and to plasma from newborn babies.DIC patients had no or very low levels of FbgDP, but high levels of other degradation products, SK-treated patients showed high levels of degradation products two hours after termination of the SK infusion. A considerable fraction of these degradation products was shown to be FbgDP. Plasma from newborn babies contained elevated levels of FbgDP associated with prolonged prothrombin times.
Keywords: Enzyme immunoassay; Primary fibrinogenolysis; Monoclonal antibodies; Fibrinogen degradation